Contingencies Ranking for Voltage Stability Analysis using Continuation Power Flow Method - Kamarposhti, M. A.; Lesani, H. (Elektronika ir Elektrotechnika, 2010)
A screening method and continuation power flow program to analyze contingencies and their impact on static voltage stability in power systems is proposed. The proposed method for contingency analysis and voltage stability studies and is based on the impact of the contingency on the load, the Mega Watt Margin (MWM) and maximum loading point. The Method provides initially a ranking scheme for first level contingencies by comparing their loadability with the maximum loadability of the system. It then makes a short list of important contingencies for detailed analysis. The proposed method is tested by the IEEE 14-bus Test System. Bibl. 14 (in English; summaries in English, Russian and Lithuanian).